On Efficient Method For Fractional-Order Two-Dimensional Navier-Stokes Equations - Jassim, Hassan; Ahmed, Hijaz; Hussein, Mohammed; Singh, Jagdev; Kumar, Devendra; Shah, Rasool; Zayir, Muslim; Cherif, Mountassir; Jabbar, Kadhim (Iraqi Journal of Science, 2024)
For the solution of fractional-order two-dimensional Navier-Stokes equations (FOTDNSEs), the current work proposes a novel variant of the Laplace Adomian decomposition approach with the Atangana-Baleanu fractional operator in the Caputo sense (ABCFO). In this approach, the solution is considered as a Taylor series expansion that converges rapidly to the exact solution. Only two components are required for the new approximation analytical technique. When compared to other strategies, the current method is very simple, requires less calculation, and is extremely accurate.